Climate and synchrony with conspecifics determine the effects of flowering phenology on reproductive success in Silene acaulis. Issue 1 (1st January 2018) - Hall, Elijah S.; Piedrahita, Lucas R.; Kendziorski, Grace; Waddle, Ellen; Doak, Daniel F.; DeMarche, Megan L.
ABSTRACT: Changes in flowering phenology resulting from climate change could impact individual plant fitness and population viability. Flowering phenology can mediate plant reproductive success in several ways, including pollinator interactions, flowering synchrony with conspecifics, and timing of suitable abiotic conditions. We explored factors that control phenology and reproductive success for an alpine cushion plant, Silene acaulis, across two years and four sites, totaling 1, 123 plants, in Colorado, USA. We investigated relationships between flowering time, flowering synchrony, and reproductive success with local abiotic conditions and pollinator behavior. Mean flowering phenology was strongly correlated with the timing of snowmelt across sites and years. Relative to mean flowering times, earlier flowering plants generally produced more flowers and experienced greater soil moisture during flowering but reduced synchrony with conspecifics. Fruit set tended to increase with greater soil moisture, synchrony during flowering, and earlier flowering times. Pollinator visitation increased with local Silene flower density. Earlier snowmelt and drier conditions later in the season favor earlier flowering, but these effects are partially counteracted by the positive effects of synchrony, perhaps because of changes in pollinator visitation. Overall, while both biotic and abiotic effects influence reproductive success, late-season drought may outweigh the benefits of flowering synchrony to increasingly favor earlier flowering.